Prevalence of thyroid dysfunctions in infants and children with Down Syndrome (DS) and the effect of thyroxine treatment on linear growth and weight gain in treated subjects versus DS subjects with normal thyroid function: a controlled study - AlAaraj, Nada; Soliman, Ashraf T; Itani, Maya; Khalil, Ahmed; De Sanctis, Vincenzo (Acta Biomedica Atenei Parmensis, 2019)
Background: Individuals with Down syndrome (DS) are at an increased risk of developing thyroid disease, primarily autoimmune, with a lifetime prevalence ranging from 13% to 63%. Unfortunately, there are few studies systematically examining the frequency of thyroid disease in very young children. Aim of the study: The aim of the present study was to investigate the prevalence of different thyroid dysfunctions (TD) in a cohort of infants and children with DS and the growth parameters in subjects with normal versus abnormal thyroid function, followed for 3 years. Patients and methods: All children (n = 102; 48 males and 54 females, aged 2.3±3 years) with the diagnosis of DS who were seen at the General Pediatric Clinic of Hamad General Hospital in Doha (Qatar) from 2014 to 2018 were enrolled in our study. We recorded thyroid function and linear growth parameters [BMI, length/height SDS (Ht-SDS) and weight gain/day] and divided them into 3 groups according to their thyroid function. Group 1: (n = 36 subjects) with normal free T4 (FT4) and TSH; Group 2 (n = 44 subjects) with high TSH >5 and <12 mIU/L, and normal FT4, and Group 3 (n = 22 subjects) with TSH >12 mIU/L and/or FT4 <9 pmol/L. We also compared linear growth parameters in subjects with DS and thyroid dysfunction versus those with normal thyroid function at diagnosis and after treatment with L- thyroxine, for an average of 3 years. Results: In infants with DS (<1 year of age; n = 47, mean age: 5±3.5 months) we documented a higher prevalence of hypothyroidism (HT) (7/47 = 14.9%), both primary (5/47; 10.6%) and secondary (2/47; 4.3%). Subclinical hypothyroidism and positive thyroid antibodies were found in (13/47; 27.7%) and (9/47;19%, respectively). Before treatment with L-thyroxine, DS infants of Group 3 had significantly lower BMI-SDS but were not significantly shorter compared to other two Groups (p= 0.03 and p =0.14, respectively). After an average of 3 years of treatment the BMI- SDS and Ht-SDS did not differ among the treated and not treated infant groups. In the older group (>1 year; n=55; mean age: 5.5±3.3 years) primary HT was detected in 7/55 (12.7%). Subclinical HT was diagnosed in 20/55 (36.4%) and positive thyroid antibodies were found in 26/55 (47.3%). Before treatment with L-thyroxine, using the CDC growth charts for DS, we found that the groups with high TSH (Groups 2 and 3) were significantly shorter and heavier compared to the group with normal TSH (Group 1). After treatment with L-thyroxine, the Ht-SDS and Wt-SDS did not differ between the two groups. The linear growth of those diagnosed early during the first year of life was compared to growth parameters of children who were diagnosed with thyroid dysfunction later in life. Conclusion: Our data provided more evidence to support the findings that L- thyroxine treatment can improve growth of infants and young DS children with high TSH (>5 mIU/L), especially in those with TSH >12 mIU/L.